Transformational Leadership, Knowledge Sharing Culture to Increase Personal Competency Development Through Knowledge Sharing Satisfaction as a Mediation Variable and Self-Efficacy as a Moderating Variable for Employees of PT. Wahana Lintas Nusantara Surabaya - Karimah, Nurul; Kusmaningtyas, Amiartuti; Ardiana, Dewa Ketut Raka (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The purpose of this study was to prove and analyze transformational leadership, knowledge sharing culture to improve personal competency development through knowledge sharing satisfaction as a mediating variable and self-efficacy as a moderating variable in employees of PT. Wahana Lintas Nusantara Surabaya. The type of research used is quantitative with an explanatory approach. The population and sample of respondents in this study amounted to 168 employees of PT. Wahana Lintas Nusantara Surabaya using saturated techniques. Data collection using gform and measured using a Likert scale. The analysis technique uses the Structural Equation Model (SEM) tool, then the Partial Least Square (PLS) and IBM SPSS 26 programs are used. The results of this study indicate that: 1). Transformational leadership has a significant positive effect on knowledge sharing satisfaction at PT. Wahana Lintas Nusantara Surabaya. 2). Knowledge sharing culture has a significant positive effect on knowledge sharing satisfaction at PT. Wahana Lintas Nusantara Surabaya. 3). Knowledge sharing satisfaction has a significant positive effect on personal competency development at PT. Wahana Lintas Nusantara Surabaya. 4). Moderating self-efficacy positively and significantly affects the satisfaction of knowledge sharing towards personal competency development. 5). Mediating satisfaction of knowledge sharing positively and significantly affects transformational leadership towards personal competency development at PT. Wahana Lintas Nusantara Surabaya. 6). Mediating satisfaction of knowledge sharing positively and significantly affects the culture of knowledge sharing towards personal competency development at PT. Wahana Lintas Nusantara Surabaya.